PENDEKATAN KEPEMIMPINAN (LEADERSHIP) YANG MENGINSPIRASI PERUBAHAN YANG FUNDAMENTAL - Danang Nugroho; Neni Nurjanah; Neng Karmila; Risma Wanti; Trian Permana Putra; Yayu Purnama Dewi (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Leadership that inspires fundamental change or is one of the leadership models often chosen by leaders in organizations. Although the definition varies according to various experts, the essence remains the same, which is to direct members to achieve common goals by emphasizing the values important to the organization. This research thoroughly investigates transformational leadership, using a qualitative approach by extracting information from the literature. The research covers various elements, including styles, attributes, traits, principles, and advantages and disadvantages, exploring various aspects from leadership styles to characteristics. This helps to understand how transformational leadership can influence organizational dynamics and identify its advantages and disadvantages in a practical context.